The ethics of germline gene editing - Gyngell, C; Douglas, T; Savulescu, J (Wiley, 2016)
Germline Gene Editing (GGE) has enormous potential both as a research tool and a therapeutic intervention. While other types of gene editing are relatively uncontroversial, GGE has been strongly resisted. In this article, we analyse the ethical arguments for and against pursuing GGE by allowing and funding its development. We argue there is a strong case for pursuing GGE for the prevention of disease. We then examine objections that have been raised against pursuing GGE and argue that these fail. We conclude that the moral case in favour of pursuing GGE is stronger than the case against. This suggests that pursuing GGE is morally permissible and indeed morally desirable.